2010
DOI: 10.1590/s1516-89132010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Solid State production of manganese peroxidases using arecanut husk as substrate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…5b). (Yasmeen et al, 2011) have observed 4.5 optimum pH, (Asalam and Asgher 2011) 4, and (Rajan et al 2010) the optimum pH of 5 for MnP activity. An optimal pH range from 4 to 7 has been observed by (de Oliveira et al 2009, Baborova et al 2006, Bermek et al 2004.…”
Section: Optimization Of Temperature Of Ligninolytic Enzymesmentioning
confidence: 97%
“…5b). (Yasmeen et al, 2011) have observed 4.5 optimum pH, (Asalam and Asgher 2011) 4, and (Rajan et al 2010) the optimum pH of 5 for MnP activity. An optimal pH range from 4 to 7 has been observed by (de Oliveira et al 2009, Baborova et al 2006, Bermek et al 2004.…”
Section: Optimization Of Temperature Of Ligninolytic Enzymesmentioning
confidence: 97%
“…Manganese dependent peroxidase is produced from P. pulmonarius, which can oxidize both non-phenolic and phenolic compounds for xenobiotic compound degradation. Kuhar and co-workers [264] have reported that MnCl 2 can induce MnP activity and has a high specificity for Mn 2+ binding sites.…”
Section: Manganese Peroxidasementioning
confidence: 99%
“…Penambahan induser pada mikroorganisme berperan untuk mengaktifkan dan meningkatkan kerja enzim (Vrsanska et al, 2015). Hal ini didukung oleh hasil penelitian Rajan et al (2010), penambahan 0,1 mM MnSO4 pada P. chrysosporium mampu meningkatkan aktivitas enzim MnP hingga 54.03 IU/L. Jika dibandingkan, aktivitas enzim MnP pada penelitian ini lebih tinggi.…”
Section: Uji Kadar Lignoselulosaunclassified